2015
DOI: 10.1007/s00421-015-3187-8
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral conduit and resistance artery function are improved following a single, 1-h bout of peristaltic pulse external pneumatic compression

Abstract: Acutely, whole limb, lower pressure EPC improves conduit artery endothelial function systemically, but only improves RH blood flow locally (i.e., compressed limbs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
4
16
0
1
Order By: Relevance
“…At the onset of the EPC treatment, all zones in the "leg 179 sleeve" are pre-inflated to form fit the participant's legs while applying minimal pressure (~10 180 mmHg). Thereafter, the distalmost chamber (which covers from the high ankle to toes) inflated Regarding AIM1 of the present investigation, the bilateral improvement in popliteal 294 artery FMD with unilateral treatment is similar to our previous observations of improved 295 popliteal (compressed leg) and brachial artery (non-compressed arm) FMD with 1-h of bilateral 296 leg EPC treatment (Martin et al 2015a). Herein, we extend our previous findings by 297 demonstrating that 1) unilateral EPC improves vascular reactivity in the treated and untreated 298 (contralateral) leg, 2) 30-min of treatment, compared to 1-h, is sufficient for improvement of 299 peripheral conduit reactivity, and 3) FMD is improved for at least 30-min following treatment.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…At the onset of the EPC treatment, all zones in the "leg 179 sleeve" are pre-inflated to form fit the participant's legs while applying minimal pressure (~10 180 mmHg). Thereafter, the distalmost chamber (which covers from the high ankle to toes) inflated Regarding AIM1 of the present investigation, the bilateral improvement in popliteal 294 artery FMD with unilateral treatment is similar to our previous observations of improved 295 popliteal (compressed leg) and brachial artery (non-compressed arm) FMD with 1-h of bilateral 296 leg EPC treatment (Martin et al 2015a). Herein, we extend our previous findings by 297 demonstrating that 1) unilateral EPC improves vascular reactivity in the treated and untreated 298 (contralateral) leg, 2) 30-min of treatment, compared to 1-h, is sufficient for improvement of 299 peripheral conduit reactivity, and 3) FMD is improved for at least 30-min following treatment.…”
supporting
confidence: 90%
“…legs) and 62 non-compressed (i.e. arms) limbs (Martin et al 2015a). Moreover, we have shown that local 63 concentration of the stable metabolites of nitric oxide (NO) are increased in skeletal muscle 64 biopsy samples following a 1-h bout of EPC (Kephart et al 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While it has been posited that EPC can exert localized vasoactive effects [5] and improve post-exercise lactate clearance [6], EPC devices are also putatively analogous to a lower-limb massage which has been shown to decrease exercise-induced inflammatory signaling [7]. Interestingly, investigators have reported that a single 15 min EPC treatment acutely improves flexibility [8] and increases the pressure-to-pain threshold (PPT) in the lower limbs following resistance training [9].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, our previous investigations exploring the molecular effects of PEPC utilized target inflation pressures of 70 mmHg given the beneficial effects seen with this pressure in vascular and sports performance studies (Martin et al. ,b). However, the effect of lower target inflation pressures with this PEPC device is unknown.…”
Section: Introductionmentioning
confidence: 99%